Thai district Leaders' perceptions of managing the direct observation treatment program in Trang Province, Thailand - Jiraporn Choowong; Per Tillgren; Maja Söderbäck (BMC, 2016)
Abstract Background Thailand is 18th out of the 22 countries with the highest tuberculosis (TB) burden. It will be a challenge for Thailand to achieve the UN Millennium Development target for TB, as well as the new WHO targets for eliminating TB by 2035. More knowledge and a new approach are needed to tackle the complex challenges of managing the DOT program in Thailand. Contextual factors strongly influence the local implementation of evidence in practice. Using the PARIHS model, the aim has been to explore district leaders' perceptions of the management of the DOT program in Trang province, Thailand. Methods A phenomenographic approach was used to explore the perceptions among district DOT program leaders in Trang province. We conducted semi-structured interviews with district leaders responsible for managing the DOT program in five districts. The analysis of the data transcriptions was done by grouping similarities and differences of perceptions, which were constructed in a hierarchical outcome space that shows a set of descriptive categories. Results The first descriptive category revealed a common perception of the leaders' duty and wish to comply with the NTP guidelines when managing and implementing the DOT program in their districts. More varied perceptions among the leaders concerned how to achieve successful treatment. Other perceptions concerned practical dilemmas, which included fear of infection, mutual distrust, and inadequate knowledge about TB. Further, the leaders perceived a need for improved management practices in implementing the TB guidelines. Conclusion Using the PARIHS framework to gain a retrospective perspective on the district-level policy implementation of the DOT program and studying the leadership's perceptions about applying the guidelines to practice, has brought new knowledge about management practices. Additional support and resources from the regional level are needed to manage the challenges.